THE ANALYSIS OF CODE SWITCHING IN ELEANOR YOUNG IN CRAZY RICH ASIANS FILM - Sumantri, Wilis Haryo; Arifin, M. Bahri; Setyowati, Ririn (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
The research focused on the types of code switching in Eleanor Young and the factors that influenced her using that code switching in Crazy Rich Asians Film. This film was about the woman who has a rich boyfriend from Singapore. Eleanor is the mother of that man. In some situation, there were some possibility that she used code switching. There are two theories that used in this research to answer two research questions. First, the researcher used the theory of types of code switching by Hoffman to analyze the type of code switching that used by Eleanor Young. Second, the researcher used theory by Hoffman to analyze the reason of the using that code switching.The data source were dialogue from Eleanor and the interlocutors in Crazy Rich Asians Film. The research design was descriptive qualitative method. The method of data collection was by collected the dialogue which categorized as code switching. The researcher provided the data in dialogues from Crazy Rich Asians film.Based on the analysis, the researcher drew two conclusion. First, this research showed Eleanor Young used inter sentinental switching, which happened between clause or sentence boundary. Second, there were three factors that influenced Eleanor Young used code switching. There were talking about particular topic, quoting somebody else, and repetition used for clarification.